Implementasi Perlindungan Hukum terhadap Aktivis Pejuang Lingkungan Hidup Berdasarkan Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup Perspektif Siyasah Dusturiyah (Studi Kasus Kabupaten Langkat) - Pasaribu, Sholie; Matondang, Maulidya Mora (Journal of Legal Sustainability, 2026)
Indonesian activists face numerous challenges in upholding the law, particularly regarding criminalization and intimidation through Strategic Lawsuits Against Public Participation (SLAPP) mechanisms. This study aims to examine the implementation of legal protection—specifically concerning land acquisition issues—under Article 66 of Law Number 32 of 2009, and to analyze it from the perspective of Siyāsah Dustūriyyah (Islamic constitutional law). The study employs a normative legal research method characterized by significant procedural and conceptual complexity. The findings indicate that the provisions of Article 66 of the Environmental Protection and Management Law (PPLH)—supported by the Regulation of the Minister of Environment and Forestry Number 10 of 2024 and the Attorney General’s Guideline Number 8 of 2022—have established a foundation for legal protection based on Anti-SLAPP principles. From the perspective of Siyāsah Dustūriyyah, these regulations align with the concept of tasharruf al-imām 'ala al-ra'iyyah manūṭun bi al-maṣlaḥah, which posits that government policy must prioritize the public interest and prevent environmental degradation. However, implementation has not been fully successful due to the absence of integrated Anti-SLAPP mechanisms within the Criminal Code and persistent power imbalances between the public and environmental activist groups.